Financial Distress Dan Audit Report Lag Pada Masa Pendemi Covid-19 - Sabella, Rizki Fani; Alfizahri, Nanda; Izfahany, Fahilla (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2021)
This research intends to analyze the impact of financial distress on audit report lagof the main board stock companies on the Indonesia Stock Exchange (IDX) duringthe Covid-19 pandemic. This research is about all entities listed in IDX are includedin the main stock listing board. Observations were made using secondary data inthe form of annual financial reports for 2020 on mainboard stock companiescollected from the official website of the Indonesia Stock Exchange (IDX)www.idx.com. The sample consists of 8 mainboard stock companies appointedthrough random sampling techniques. The classic assumption test is used inanalyzing the data and simple regression analysis was used through the IBM SPSS26 application to analyze the hypothesis. The results of statistical tests arefinancial distress has a positive impact on audit report lag during the covid-19pandemic. The Covid-19 pandemic has an impact on the decline in companyfinancial stability and makes the company experience financial difficulties whichmake the company's audit risk high so that it has an impact on the duration offinancial statement examination required by auditors.